Transient Stability Improvement Using Coordinated Control of Solar PVs and Solid State Transformers - Panya Khemmook; Surin Khomfoi (My University, 2018)
An optimization coordinated controller applied for solar farm together with a solid state transformer in order to improve transient stability is presented in this paper. Transient stability issues in a modern electrical power grid represent one of the challenge topics for an electrical engineer because uncertain renewable energy resources (RES) are increased because of a demand for green energy requirement. This increased RES can adversely disturb a terminal voltage; consequently, a damage to electrical equipment can happen. In order to solve a transient response issue, it is possible to use a solid state transformer (SST) or intelligent transformer, used to interface between RES and a power grid. SST consists of a set of converters which can be modulated via the converters to maintain the desired voltage levels; thus, this solution can reduce transient response and power fluctuation concurrently. For this reason, this paper presents a controller design for a solar photovoltaic (SPV), connected to a power grid via SST in order to enhance the quality of power injections from RES to improve transient stability of the electrical system. The optimization of a controller model is proposed by modifying a PI controller from a commercial one. The proposed controller is validated with the standard IEEE 39 buses. The validation scenario of both an uncertainty due to time delay accounting for a range of 425ms-525ms and various solar radiation patterns are also taken into account for the evaluation of a proposed controller performance. Simulation results demonstrate that power fluctuation due to uncertain RES can be mitigated by using the proposed controller. Moreover, in case of large disturbances such as a circuit breaker tripping to open a power line due to a fault, the proposed coordinated control of SPV and SST can satisfactorily perform to suppress severe voltage swings within an electrical device rated voltage limit to protect catastrophe damage. The results suggest that the proposed controllers can be alternative solutions in order to solve a transient stability issue due to uncertain increased RES in a modern power grid.
Keywords: Transient (computer programming); Photovoltaic System Optimization Techniques